Rearward Visibility Assessment and a Proposed Performance Scoring for ASEAN NCAP - Abd Rahman, B.; Mohd Sohimin, M.H.F.; Meor Said, M.A.; Tuan Kamaruddin, T.N.A.; Abu Husain, N.; Mohamad Jamil, S.N.; Balaka, R.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Asia has the highest number of registered motorcycles globally, and the recent data has shown that motorcycles fatalities have been the main road death category in the Southeast Asian region. One of the major concerns is the visibility of motorcycles to other vehicles on the road. Thus, in this project, UN R46 and FMVSS regulations have been referred to as the base guidelines to establish a novel test protocol for vehicles rearward visibility assessment. Sixteen cars have been benchmarked and analysed in terms of their rear-view mirror (Class I) and external mirror (Class III) performance. Motorcycles visibility to the vehicles’ Class I and Class III mirrors also been assessed by converting the measured data into several motorcycles based on its width. A proposed performance scoring system for ASEAN NCAP has been developed based on that to address the Motorcycle Safety pillar.